2020
DOI: 10.1371/journal.pone.0242435
|View full text |Cite|
|
Sign up to set email alerts
|

Mathematical modelling and control of African animal trypanosomosis with interacting populations in West Africa—Could biting flies be important in main taining the disease endemicity?

Abstract: African animal trypanosomosis (AAT) is transmitted cyclically by tsetse flies and mechanically by biting flies (tabanids and stomoxyines) in West Africa. AAT caused by Trypanosoma congolense, T. vivax and T. brucei brucei is a major threat to the cattle industry. A mathematical model involving three vertebrate hosts (cattle, small ruminants and wildlife) and three vector flies (Tsetse flies, tabanids and stomoxyines) was described to identify elimination strategies. The basic reproduction number (R0) was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Trypanosoma brucei brucei , a subspecies of the genus T. brucei , infects a variety of animals in Africa and causes widespread epidemics of African animal trypanosomosis (also known as trypanosomiasis or Nagana; Guerrini and Bouyer, 2007 ; Latif et al, 2019 ; Odeniran et al, 2020 ). African animal trypanosomiasis is transmitted by tsetse flies into the hosts during blood-sucking and the infected animals suffer from wasting, anemia, neurological symptoms, and even death ( Osaer et al, 1999 ; Diarra et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Trypanosoma brucei brucei , a subspecies of the genus T. brucei , infects a variety of animals in Africa and causes widespread epidemics of African animal trypanosomosis (also known as trypanosomiasis or Nagana; Guerrini and Bouyer, 2007 ; Latif et al, 2019 ; Odeniran et al, 2020 ). African animal trypanosomiasis is transmitted by tsetse flies into the hosts during blood-sucking and the infected animals suffer from wasting, anemia, neurological symptoms, and even death ( Osaer et al, 1999 ; Diarra et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of models used the same frameworks for both the domestic and wildlife populations, though five articles used different model frameworks for each species. Here, network models for domestic species were used in combination with a wildlife metapopulation model ( 49 ) or PBM ( 50 ), or domestic IBMs were used with a wildlife metapopulation model ( 51 ) or wildlife PBMs ( 39 , 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…The predicted effects of different strategies to control animal African trypanosomiasis (AAT) were also recently explored using modelling approaches. These data indicated that insecticidal treatment of cattle alone could eliminate T. brucei from the local population, but that it would have little effect on two other species, namely T. congolense and T. vivax , which are maintained in reservoirs such as wildlife and small ruminants [ 90 ].…”
Section: Evolutionary Implications and Areas That Need Developmentmentioning
confidence: 99%